Weapon-carrying among young men in Glasgow: street scripts and signals in uncertain social spaces - Holligan, Chris (Critical criminology, 2017)
Our work contributes through a cultural criminological perspective to a contextualised knowledge of street violence and its constructed meanings; uncertainty, familiarity and strangeness in spaces of urban disadvantage as perceived by Scottish white youths are examined. Youth criminal and anti-social behaviour associated with knife-carrying is widely reported and structures political and media discourses which classify street culture. In our article we argue that a particular symbolic construction of social space, as experienced and constructed by weapon-carrying young white men in Glasgow, informs the landscape of violence judged in terms of official statistics and fear of crime. Signal crime theory as a particular type of cultural criminology affords insights about why weapons are carried. Links with a hierarchical codification of consumer culture inform the findings and resonate with the penetration of capitalism in the lives of the marginalised street youth.